The long way ahead to achieve an effective patient safety culture: challenges perceived by nurses - Jamileh Farokhzadian; Nahid Dehghan Nayeri; Fariba Borhani (BMC, 2018)
Abstract Background The safety culture has recently attracted the attention of healthcare organizations. Considering the importance of the roles of nurses with regard to patient safety, their knowledge and experiences of the challenges that influence patient safety culture can facilitate the development and implementation of better strategies. The aim of this study was to explore the nurses' experiences of the challenges influencing the implementation and integration of safety culture in healthcare. Methods A qualitative study with deep and semi-structured individual interviews was carried out using a purposive sampling method to select 23 nurses from four hospitals affiliated with a large medical university in Southeast Iran. Data were analysed using the conventional content analysis of Lundman and Graneheim. Results Data analysis reflected the main theme of the study, "A long way ahead of safety culture". This theme includes four categories: 1) inadequate organizational infrastructure, 2) insufficient leadership effectiveness, 3) inadequate efforts to keep pace with national and international standards, and 4) overshadowed values of team participation. Conclusion While practical strategies for creating a safety culture may seem simple, their implementation is not necessarily easy. There are several challenges ahead for cultivating an effective and positive safety culture in healthcare organizations. To keep pace with international standards, healthcare managers must employ modern methods of management in order to overcome the challenges faced by the institutionalization of safety culture and to make a difference in the healthcare system.